Individual variation in mouthfeel sensitivity: investigating influences of whey protein content, consumer age, food format and fat addition. (October 2022) - Norton, Victoria; Lignou, Stella; Faka, Marianthi; Methven, Lisa
Highlights: A mouthdrying detection threshold for whey protein was established. Individuals differ in mouthdrying thresholds. Mouthfeel sensitivity differs between younger and older adults. Lubrication suppressed mouthdrying in protein fortified scones, regardless of consumer age. Abstract: Individual sensitivity to whey protein derived mouthdrying can vary with protein level and age; however, to date no thresholds for this have been established. Additionally, previous research suggests that increasing fat in whey protein solid models can enhance lubrication and suppress mouthdrying, but this needs testing in older adults. Here, a trained sensory panel ( n  = 10) determined a mouthdrying detection threshold (MDT) in whey protein beverages (WPB). To compare sensitivity between younger and older adults ( n  = 116; 18–30; 65+): (1) WPB just-noticeable difference (JND) thresholds were established and (2) liking and perception of whey protein fortified beverages and scones were rated. The trained panel detected mouthdrying at all protein levels (0.14% to 10.0% w/v) with the MDT being established between 0.41% (50% discriminators) and 1.37% (Best Estimate Threshold, BET) w/v protein. The JND mouthdrying threshold was significantly lower ( p  = 0.02) in older adults compared with younger adults (0.75% versus 0.90% w/v protein; BET). Increasing protein levels in WPBs significantly increased mouthdrying and reduced liking and easiness to consume (utilising rating scales). Whey protein fortified scones with cream topping significantly increased liking, easiness to consume, sweetness, moistness and rate of clearance and reduced mouthdrying and chewiness. Older adults perceived WPBs as significantly easier to consume and the scones significantly chewier than younger adults. Age-related mouthfeel effects and individual differences in mouthdrying sensitivity are key factors for product design.